Effects of codon usage on gene expression are promoter context dependent. Issue 2 (7th January 2021) - Yang, Qian; Lyu, Xueliang; Zhao, Fangzhou; Liu, Yi
Abstract: Codon usage bias is a universal feature of all genomes. Although codon usage has been shown to regulate mRNA and protein levels by influencing mRNA decay and transcription in eukaryotes, little or no genome-wide correlations between codon usage and mRNA levels are detected in mammalian cells, raising doubt on the significance of codon usage effect on gene expression. Here we show that gene-specific regulation reduces the genome-wide codon usage and mRNA correlations: Constitutively expressed genes exhibit much higher genome-wide correlations than differentially expressed genes from fungi to human cells. Using Drosophila S2 cells as a model system, we showed that the effect of codon usage on mRNA expression level is promoter-dependent. Regions downstream of the core promoters of differentially expressed genes can repress the codon usage effects on mRNA expression. An element in the Hsp70 promoter was identified to be necessary and sufficient for this inhibitory effect. The promoter-dependent codon usage effects on mRNA levels are regulated at the transcriptional level through modulation of histone modifications, nucleosome densities and premature termination. Together, our results demonstrate that promoters play a major role in determining whether codon usage influences gene expression and further establish the transcription-dependent codon usage effects on gene expression.